2012
DOI: 10.1021/ac202508u
|View full text |Cite
|
Sign up to set email alerts
|

Use of Negative Dielectrophoresis for Selective Elution of Protein-Bound Particles

Abstract: In this paper with the aid of negative dielectrophoresis force in conjuction with shear force and at an optimal sodium hydroxide concentration we demonstrated a switch-like functionality to elute specifically-bound beads from the surface. At an optimal flow rate and sodium hydroxide concentration, negative dielectrophoresis turned on results in bead detachment, whereas when negative dielectrophoresis is off, the beads remain attached. This platform offers the potential for performing a bead-based multiplexed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…12–14 Another advantage, given the micron size of beads is that one can better control the force applied to beads and thus measure the affinity of biomolecules’ interactions. This has previously been shown using shear force 15 , optical tweezers 16 , magnetic tweezers 17 , and more recently electrokinetic forces 1821 . Electronic force provides the advantage of scalability and precise addressability when multiplexing.…”
Section: Introductionmentioning
confidence: 57%
“…12–14 Another advantage, given the micron size of beads is that one can better control the force applied to beads and thus measure the affinity of biomolecules’ interactions. This has previously been shown using shear force 15 , optical tweezers 16 , magnetic tweezers 17 , and more recently electrokinetic forces 1821 . Electronic force provides the advantage of scalability and precise addressability when multiplexing.…”
Section: Introductionmentioning
confidence: 57%
“…Traditionally, electrokinetic techniques such as dielectrophoresis are characterized by relatively weak forces (less than 10 pN) [34,35] which are, often insufficient for separation processes. The DEP force is given by the following equation to first order: FDEP=2πϵ0ϵmr3Re{fCM}ERMS2, where ε m is the relative permittivity of the surrounding medium, r is the particle radius, and E RMS is the root-mean-square value of the electric field.…”
Section: Enhanced Dielectrophoresis (Dep) For Particle Depletionmentioning
confidence: 99%
“…Depending on the conductivity of the buffer, this will vary for both cells and beads. In our previous work [35], we calculated the DEP spectrum and determined that for a buffer conductivity greater than 5 × 10 −4 S/m for polystyrene beads (dielectric constant of 2.5), the CM factor will be negative across the whole frequency spectrum. Castellarnau et al [36] also calculated the DEP spectrum for bacterial cells in buffers of various conductivities, and showed that for conductivities greater than 0.1 S/m, at f = 1 MHz, the CM factor will be negative.…”
Section: Enhanced Dielectrophoresis (Dep) For Particle Depletionmentioning
confidence: 99%
“…Various miniaturization techniques have been introduced for detection of proteins [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], nucleic acids [10,16,21], and cells [22][23][24][25][26][27]. These techniques are unsuitable for metabolites because tagging the metabolite with beads or a fluorophore would alter the structure significantly and affect the binding of the target metabolite to the probe antibody.…”
Section: Metabolite Detectionmentioning
confidence: 99%